Behaviours preceding suicides at railway and underground locations: a multimethodological qualitative approach. Issue 4 (10th April 2018) - Mackenzie, Jay-Marie; Borrill, Jo; Hawkins, Emily; Fields, Bob; Kruger, Ian; Noonan, Ian; Marzano, Lisa
Abstract : Objectives: Suicides by train have devastating consequences for families, the rail industry, staff dealing with the aftermath of such incidents and potential witnesses. To reduce suicides and suicide attempts by rail, it is important to learn how safe interventions can be made. However, very little is known about how to identify someone who may be about to make a suicide attempt at a railway location (including underground/subways). The current research employed a novel way of understanding what behaviours might immediately precede a suicide or suicide attempt at these locations. Design and methods: A qualitative thematic approach was used for three parallel studies. Data were gathered from several sources, including interviews with individuals who survived a rail suicide attempt (n=9), CCTV footage of individuals who died by rail suicide (n=16) and qualitative survey data providing views from rail staff (n=79). Results: Our research suggests that there are several behaviours that people may carry out before a suicide or suicide attempt at a rail location, including station hopping and platform switching, limiting contact with others, positioning themselves at the end of the track where the train/tube approaches, allowing trains to pass by and carrying out repetitive behaviours. Conclusions: There are several behaviours that may be identifiable in the moments leading up to a suicide or suicide attempt on the railways which may present opportunities for intervention. These findings have implications for several stakeholders, including rail providers, transport police and other organisations focused on suicide prevention.